Historically revealing : a cultural analysis of four recovered plays by Irish women, 1900-1925 - O'Donoghue Greene, Mary Elizabeth Velma (Trinity College (Dublin, Ireland). Department of Drama, 2012)
This thesis concerns the retrieval and analysis of four plays written in two distinct collaborative configurations by early twentieth-century Irish women, Geraldine Cummins (1890-1968), Susanne Day (1876-1964) and Hester Travers Smith (née Dowden 1869-1949). The focus on these previously un-critiqued playwrights emerged from consideration of 28 plays and associated material uncovered in the ‘Geraldine Cummins Collection’ in the Cork City & County Archives. The project takes a multi-disciplinary feminist approach using a four-chapter structure to examine the paired collaborations of Cummins and Day, and of Dowden and Cummins; their contribution to the emergent Irish theatre movement and the relation of their work to Irish cultural and feminist discourses.
Keywords: Drama, Ph.D.; Ph.D. Trinity College Dublin